BIOMOLECULAR MECHANISM OF ANTI EPILEPTIC DRUGS - Husna, Machlusil; Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2018)
Epilepsy therapy is almost always chronic and often used more than one drug. Currently, antiepileptic drugs are still the mainstay of therapy for epilepsy. An understanding of the pharmacodynamics and pharmacokinetics of these drugs would be very helpful in choosing the right medication and develop a study to determine the drugs mechanism further. Mechanism of action of AED (anti epileptic drug) can be categorized into four main groups: (1) modulation of voltage-gated ion channels, including sodium, calcium, and potassium; (2) increase in GABA inhibition through an effect on GABA-A receptors, the GAT-1 GABA transporter, or GABA transaminase; (3) direct modulation of the synaptic release of such SV2A and Î±2Î´; and (4) inhibition of excitatory synapses through ionotropik glutamate receptors including AMPA receptors. AED work to balance the process of inhibition and excitation in the brain, so it can be used both for epilepsy and other diseases with similarities with the pathophysiology of epilepsy.